Nutritional deficiencies among school children in urban areas of Hyderabad, Telangana, India - Chajhlana, Sunil Pal Singh; Mahabhasyam, Ramakrishna Narashimha; Varaprasada, Maruti Sarma Mannava (International Journal Of Community Medicine And Public Health, 2017)
Background: The school age period is nutritionally significant because this is the prime time to build up body stores of nutrients in preparation for rapid growth of adolescence. Malnutrition remains the world’s most serious health problem and the single biggest contributor to child mortality, nearly one third of the children in the developing world are either underweight or stunted and more than 30% of the developing world’s population suffer from micronutrient deficiencies. However the data available from urban slums of Hyderabad in this age group is very sparse and hence an attempt has been made to study the same. The objectives were to determine the nutritional status of primary school children and study the factors associated with it. Methods:Study population: Primary school children (6 to 11 years). Study area: primary schools in urban slums of Hyderabad. Study design: a cross sectional study. Sample size: 412 children. Sampling methods: Simple random sampling Data collection: By using pre designed and pre tested and pre coded schedule (interview technique, observation, clinical examination). Analysis: By using Microsoft Excel 2007 and Epi Info 3.5.3. Results: The prevalence of underweight was 28.9%, overweight was 9.2% and obesity was 4.4% . Prevalence of stunted height was found among 21.8%. 5.8% children were suffering from Vitamin’ A’ deficiency, 15.0% were suffering from Vitamin B deficiency, and 15.8% were found to be anemic. Conclusions:The prevalence of underweight, Nutritional deficiencies were found to be significantly higher in children of illiterate parents’ and similarly in unskilled worker fathers’ and unemployed mothers.